Caracterização da morbidade dos pacientes com doença de Chagas no Estado do Ceará - Jacó, José Igor de Oliveira (2023)
INTRODUCTION: Chagas disease (CD), discovered more than a century ago, still represents a serious public health problem in Latin America, being considered a neglected disease that affects the population of low socioeconomic status and responsible for a high burden of morbidity and mortality in countries. In this context, we emphasize the need to characterize the morbidity and mortality of patients with CD followed up in a pharmaceutical care service during the period from 2005 to 2020 and to characterize the mortality of CD disease in the state of Ceará in the same period. METHODOLOGY: To assess morbidity, patient records from the pharmaceutical care service were used (n=569). For mortality, data were obtained from the national information system on mortality (SIM), which is publicly accessible (n= 809). RESULT: : The profile of patients followed up at the pharmaceutical care service was characterized with a mean age of 59 years, male n=293 (51.5%), farmer n=144 (25.3%), family income less than 3 minimum wages n=399 (70.1%), from rural areas n=280 (49.2%) and continued to reside in the municipalities of Vale do Jaguaribe n=262 (46%). The most prevalent chronic form was the undetermined one with n=439 (77.2%), 351 (61.7%) of the patients had at least one comorbidity, highlighting those that affected the cardiovascular system. In the service, 15 patients died, of which 11 (73.3%) were male, with cardiac involvement as the main cause of death with n=11 (73.3%) and associated cause with higher prevalence of pneumonia not specified with n=4 (26.6%). The lethality rate in the pharmaceutical care service was 2.6%. The CD mortality rate in the state of Ceará presented an average of 5.8 deaths/1,000,000 inhabitants, being higher in males. The patients who died were characterized as male with n=538 (66.5%), with a mean age of 66 years, of brown ethnicity n=530 (65.5%), with incomplete primary education n=630 (77.9%), farming profession n=366 (45.2%) and residing in Vale do Jaguaribe n=163 (20.1%). The main cause of death was cardiac impairment with n=617 (76.3%) and as the main associated cause cardiogenic shock n=111 (13.7%). CONCLUSION: CD represents a serious public health problem due to the various injuries caused by this disease and the characteristics related to its chronicity profile. Knowing the current context of this disease in a historically endemic area, the state of Ceará, contributes to the prevention of serious adverse events.